Design, Synthesis, and Biological Evaluation of Novel Fluorescent Probes Targeting the 18‐kDa Translocator Protein. (24th March 2021) - Wongso, Hendris; Yamasaki, Tomoteru; Kumata, Katsushi; Ono, Maiko; Higuchi, Makoto; Zhang, Ming‐Rong; Fulham, Michael J.; Katsifis, Andrew; Keller, Paul A.
Abstract: A series of fluorescent probes from the 6‐chloro‐2‐phenylimidazo[1, 2‐ a ]pyridine‐3‐yl acetamides ligands featuring the 7‐nitro‐2‐oxa‐1, 3‐diazol‐4‐yl (NBD) moiety has been synthesized and biologically evaluated for their fluorescence properties and for their binding affinity to the 18‐kDa translocator protein (TSPO). Spectroscopic studies including UV/Vis absorption and fluorescence measurements showed that the synthesized fluorescent probes exhibit favorable spectroscopic properties, especially in nonpolar environments . In vitro fluorescence staining in brain sections from lipopolysaccharide (LPS)‐injected mice revealed partial colocalization of the probes with the TSPO. The TSPO binding affinity of the probes was measured on crude mitochondrial fractions separated from rat brain homogenates in a [ 11 C]PK11195 radioligand binding assay. All the new fluorescent probes demonstrated moderate to high binding affinity to the TSPO, with affinity ( K i ) values ranging from 0.58 nM to 3.28 μM. Taking these data together, we propose that the new fluorescent probes could be used to visualize the TSPO. Abstract : Towards monitoring neuroinflammation and ‐degeneration : A series of TSPO‐targeted probes based on 6‐chloro‐2‐phenylimidazo[1, 2‐a]pyridine‐3‐yl acetamide ligands with a NBD fluorophore has been designed and synthesised. Their efficacy was assessed in a competitive binding assay on TSPO receptors against [ 11 C]PK11195. The probe with the most potential can be considered to be eligible for investigating activated microglia.